Adolescent preferences for weight terminology used by health care providers. Issue 9 (24th March 2018) - Puhl, R. M.; Himmelstein, M. S.
Summary: Background: In light of high rates of obesity and weight stigma in youth, the American Academy of Paediatrics recommends that paediatric health care professionals use appropriate, sensitive and non‐stigmatizing language in communication about weight with youth. For these efforts to be effective, there is a need to identify weight‐based language preferences among youth with overweight and obesity, as research in this area is scarce. Objectives: The present study provides a systematic assessment of youth perspectives of weight‐based language used by providers. Methods: Adolescents (ages 13–18 years; N  = 148) enrolled in a national weight loss camp were surveyed about their preferences for words that health providers use to refer to their body weight. Adolescents completed an online survey and responded to a list of 16 words describing excess body weight, as well as questions assessing demographics, body mass index, and experienced as well as internalized weight stigma. Results: Adolescents assigned low ratings to words like 'fat', 'large', 'obese' and 'extremely obese', indicating that they would not want providers to use these words when discussing their body weight. In contrast, words like 'weight problem', 'BMI' and 'plus size' were rated among the most preferred words for providers to use. Word preferences varied across gender, body mass index and extent of internalized weight stigma. Conclusions: These findings underscore the importance of acknowledging different word preferences among youth, and to avoid making assumptions about what words youth will feel most comfortable using in discussions about their body weight.